Student Satisfaction in University Students: A Systematic Review of the Literature - Mireles Vázquez, Mariel Guadalupe (2022)
Satisfaction is the pleasant state that the individual is in when they feel their expectations are covered; in the student sphere, it refers to the degree of well-being that students perceive when their expectations and academic needs are met. The objective of this study is to systematically review the available literature on student satisfaction. Methodology: The review was carried out by describing the year of publication, the year of completion, country of origin, academic degree, instrument, design, number of participants, age ranges, gender, and outstanding factors of student satisfaction in order to generate interest in the subject for future studies. A systematic review was conducted to identify studies related to student satisfaction. The RedALyC, Scielo, and Scopus databases were analyzed. Articles from 2015 to 2021were searched for during a random week in April of 2021, using student satisfaction as the search term. Results: the review carried out showed that during 2019 there was greater publication on the topic, Latin American countries have the largest number of publications, with mixed analysis, with undergraduate students being the most studied through questionnaires. Conclusions: the most important components of student satisfaction were: the good image and quality of the institution, teaching, tutoring and motivation. This study has practical implications because it allows identifying the components that globally impact student satisfaction and therefore provides information that can be used to make more efficient school decisions and solve educational problems associated with school stress, dropout rate and poor academic performance. It is recommended to continue carrying out research on the subject. This will allow the creation of a broader body of knowledge that integrates the new educational realities caused by the COVID-19 pandemic.